Contacts and interaction proceedings of the 27th Congress of the Union Europeenne des Arabisants et Islamisants Helsinki 2014 - Hameen-Anttila, Jaakko; Koskikallio, Petteri; Lindstedt, Ilkka (Orientalia Lovaniensia analecta, 2017)
"The Proceedings of the 27th congress of the Union Européenne des Arabisants et Islamisants (Helsinki, Finland, June 2-6, 2014) contain forty-three scholarly articles on various aspects of the Islamic world from late antiquity to modernity. The scholarly focus of most contributions is the medieval Musliim civilisation. In addition to the Arabic cultural sphere, the Persian and Turkish regions are represented in this collection of articles. The studies discuss social, political, literary and cultural history. The variety of approaches to the sources and methods employed shows the width of European research on the Arab-Islamic culture. This volume provides an easy access to the newest European scholarship on the Middle East."--